(untitled) (Web of Teachers: Inderscience Research, 2025)
The article provides an in-depth analysis of the role of the human factor in production processes. Safety culture, stress management, professional competence, and psychological stability play a crucial role in worker efficiency and safety. The article also examines methods for forming effective teams, leadership, and communication to reduce errors. Proper management of the human factor contributes to enhancing safety and improving the professional environment in production. Both theoretical and practical aspects are covered.